Pelatihan Manajemen Keuangan dan Inovasi Kewirausahaan sebagai Upaya Peningkatan Pendapatan Keluarga pada Ibu-Ibu Rumah Tangga RW 04 Prenggan Kotagede Yogyakarta - Ainun Hertikasari; Niken Permatasari; Wuku Astuti; Sarimutiara Tumanggor; Kholifi Kholifi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
Housewives in Tinalan GK II RW 04 Prenggan Kotagede Yogyakarta are business actors who manage their businesses with inadequate skills, especially in terms of financial management and recording, as well as entrepreneurial innovation. Financial management is an important aspect for the progress of family entrepreneurship. This is because the actors are faced with the problem of human resource capabilities in financial management and recording. Financial management and recording can be done through accounting, although in this case the standards used are basic and simple. On the other hand, entrepreneurial innovation related to packaging design and marketing is another major problem. Based on these problems, this community service aims to improve the insight, knowledge, and skills of housewives in Tinalan KG II RW 04 Prenggan, Kotagede District, Yogyakarta City in financial management and recording in entrepreneurship and entrepreneurial innovations that need to be done for their businesses.